Efficacy of anti-PD-1 and ipilimumab alone or in combination in acral melanoma. Issue 7 (6th July 2022) - Bhave, Prachi; Ahmed, Tasnia; Lo, Serigne N; Shoushtari, Alexander; Zaremba, Anne; Versluis, Judith M; Mangana, Joanna; Weichenthal, Michael; Si, Lu; Lesimple, Thierry; Robert, Caroline; Trojanello, Claudia; et al.
Abstract : Background: Acral melanoma is a rare melanoma subtype with poor prognosis. Importantly, these patients were not identified as a specific subgroup in the landmark melanoma trials involving ipilimumab and the anti-programmed cell death protein-1 (PD-1) agents nivolumab and pembrolizumab. There is therefore an absence of prospective clinical trial evidence regarding the efficacy of checkpoint inhibitors (CPIs) in this population. Acral melanoma has lower tumor mutation burden (TMB) than other cutaneous sites, and primary site is associated with differences in TMB. However the impact of this on the effectiveness of immune CPIs is unknown. We examined the efficacy of CPIs in acral melanoma, including by primary site. Methods: Patients with unresectable stage III/IV acral melanoma treated with CPI (anti-PD-1 and/or ipilimumab) were studied. Multivariable logistic and Cox regression analyses were conducted. Primary outcome was objective response rate (ORR); secondary outcomes were progression-free survival (PFS) and overall survival (OS). Results: In total, 325 patients were included: 234 (72%) plantar, 69 (21%) subungual and 22 (7%) palmar primary sites. First CPI included: 184 (57%) anti-PD-1, 59 (18%) anti-PD-1/ipilimumab combination and 82 (25%) ipilimumab. ORR was significantly higher with initial anti-PD-1/ipilimumab compared with anti-PD-1 (43% vs 26%, HR 2.14, p=0.0004) and significantly lower with ipilimumab (15% vs 26%, HR 0.49, p=0.0016). Landmark PFS at 1 year was highest for anti-PD-1/ipilimumab at 34% (95% CI 24% to 49%), compared with 26% (95% CI 20% to 33%) with anti-PD-1 and 10% (95% CI 5% to 19%) with ipilimumab. Despite a trend for increased PFS, anti-PD-1/ipilimumab combination did not significantly improve PFS (HR 0.85, p=0.35) or OS over anti-PD-1 (HR 1.30, p=0.16), potentially due to subsequent therapies and high rates of acquired resistance. No outcome differences were found between primary sites. Conclusion: While the ORR to anti-PD-1/ipilimumab was significantly higher than anti-PD-1 and PFS numerically higher, in this retrospective cohort this benefit did not translate to improved OS. Future trials should specifically include patients with acral melanoma, to help determine the optimal management of this important melanoma subtype.